2021
DOI: 10.1038/s41598-021-01418-9
|View full text |Cite
|
Sign up to set email alerts
|

Tunable control of CAR T cell activity through tetracycline mediated disruption of protein–protein interaction

Abstract: Chimeric antigen receptor (CAR) T cells are a promising form of cancer immunotherapy, although they are often associated with severe toxicities. Here, we present a split-CAR design incorporating separate antigen recognition and intracellular signaling domains. These exploit the binding between the tetracycline repressor protein and a small peptide sequence (TIP) to spontaneously assemble as a functional CAR. Addition of the FDA-approved, small molecule antibiotic minocycline, acts as an “off-switch” by displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…(40,41) Fab-based CARs have been previously described (42) and their increased stability has been exploited to improve CAR performance. (43) With this structure, we were able to produce CARs capable of CD21-speci c lysis and cytokine release in vitro. We found that converting proximal targeting CARs to a Fab format reduced tonic signalling and improved performance, resulting in a nal aCD21 CAR candidate effective in clinically relevant in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…(40,41) Fab-based CARs have been previously described (42) and their increased stability has been exploited to improve CAR performance. (43) With this structure, we were able to produce CARs capable of CD21-speci c lysis and cytokine release in vitro. We found that converting proximal targeting CARs to a Fab format reduced tonic signalling and improved performance, resulting in a nal aCD21 CAR candidate effective in clinically relevant in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative could be designing reversible off/on-switches that permit temporal control of CAR T cell activation and preserve antitumour function [138][139][140] . Several designs have been proposed to date, many of which rely on the administration of small molecules 109,141,142 or antibodies 143 , among other methods [144][145][146] .…”
Section: Review Articlementioning
confidence: 99%
“…Their results demonstrated that CD4 CAR T cells have robust antitumor activities in vivo, and CAR T cells were depleted 24 h after CAMPATH treatment in different organs. In addition, bridging to an allogeneic HSCT following CAR T-cell therapy and using short-lived effector cells instead of T cells have been shown to be valid methods to prevent T-cell aplasia, with both strategies succeeding in clinical studies [ 89 , 90 ].…”
Section: T-cell Aplasia and Proposed Solutionsmentioning
confidence: 99%